Action potential–independent spontaneous microdomain Ca 2+ transients–mediated continuous neurotransmission regulates hyperalgesia - Zhuoyu Zhang; Jingyu Yao; Jingxiao Huo; Ruolin Wang; Xueting Duan; Yang Chen; Huadong Xu; Changhe Wang; Zuying Chai; Rong Huang (Proceedings of the National Academy of Sciences, 2025)
Neurotransmitters and neuromodulators can be released via either action potential (AP)–evoked transient or AP-independent continuous neurotransmission. The elevated AP-evoked neurotransmission in the primary sensory neurons plays crucial roles in hyperalgesia. However, whether and how the AP-independent continuous neurotransmission contributes to hyperalgesia remains largely unknown. Here, we show that primary sensory dorsal root ganglion (DRG) neurons exhibit frequent spontaneous microdomain Ca 2+ (smCa) activities independent of APs across the cell bodies and axons, which are mediated by the spontaneous opening of TRPA1 channels and trigger continuous neurotransmission via the cyclic adenosine monophosphate-protein kinase A signaling pathway. More importantly, the frequency of smCa activity and its triggered continuous neurotransmission in DRG neurons increased dramatically in mice experiencing inflammatory pain, inhibition of which alleviates hyperalgesia. Collectively, this work revealed the AP-independent continuous neurotransmission triggered by smCa activities in DRG neurons, which may serve as a unique mechanism underlying the nociceptive sensitization in hyperalgesia and offer a potential target for the treatment of chronic pain.